2017
DOI: 10.1371/journal.pone.0178122
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rubella immunization rates in immigrant and Italian women of childbearing age: Results from the Italian behavioral surveillance system PASSI (2011-2015)

Abstract: BackgroundInternational migration rapidly increased in the last decade, raising a renewed attention to its impact on public health. We evaluated differences in rubella immunization rate (RIR) between immigrant and Italian women of childbearing age and tried to identify the driving factors causing them.MethodsWe analyzed data from the Italian behavioral surveillance system PASSI collected in 2011–2015 in a nationally representative sample of residents in Italy. The analysis was performed using log-binomial mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…In this study, women born abroad seem to be well represented due to their frequent access to hospital care for VTP and delivery procedures, but our data showed differences to that extracted from the last surveys on serological status among childbearing immigrants in Italy (Fabiani et al, 2017; Lo Giudice et al, 2014; De Paschale et al, 2012). We may speculate that it was probably due to their epidemiological characteristics, possibly related to both origin from not-high migratory pressure countries and sufficient length-of-stay in Italy contributing to higher responsiveness to public health agenda targets.…”
Section: Discussioncontrasting
confidence: 72%
“…In this study, women born abroad seem to be well represented due to their frequent access to hospital care for VTP and delivery procedures, but our data showed differences to that extracted from the last surveys on serological status among childbearing immigrants in Italy (Fabiani et al, 2017; Lo Giudice et al, 2014; De Paschale et al, 2012). We may speculate that it was probably due to their epidemiological characteristics, possibly related to both origin from not-high migratory pressure countries and sufficient length-of-stay in Italy contributing to higher responsiveness to public health agenda targets.…”
Section: Discussioncontrasting
confidence: 72%
“…We did not identify a strong overall association with gender/sex or age in the data. Seven (24,41,42,44,45,79,80) out of 10 studies found no association with gender/sex and seven (28,29,42,75,79,81,85) out of 16 studies found no association with age. Of the nine studies reporting an association with age, the direction of association varied across samples, and the broadly different reference groups mean it is not possible to draw reliable conclusions.…”
Section: Determinants Of Under-vaccination In Migrant Populationsmentioning
confidence: 93%
“…Thirty-seven studies (23, 24, 28-30, 41, 42, 44, 45, 47, 49, 51, 59, 67-90) (70,81); Syria (30,44); Iraq (44,47); Afghanistan (47,81); Iran (47)); six studies with Asian origin (28,70,72,74,86,89), and two studies with Central/South America origin (73, 74) (See Table 4 for full list of associations). Six (28,29,75,(79)(80)(81) out of eight studies found that under-vaccination was significantly associated with more recent migration to the host country (28,29,75,79,81) or lower acculturation with the host society (80).…”
Section: Determinants Of Under-vaccination In Migrant Populationsmentioning
confidence: 99%
See 2 more Smart Citations